Factors affecting the deterioration of ball attachment system on dental implants in patients with implant-retained mandibular overdentures “Khao Aroi,” Kamphaeng Phet hospital - Pornprapapan, Sirirat (Journal of Nakornping Hospital, 2022)
Objective: To identify factors affecting the deterioration of ball attachment system on dental implants in patients with implant-retained mandibular overdentures “Khao Aroi” in Kamphaeng Phet hospital. Method of the study: This study was a retrospective study in 67 patients who were implanted with implant-retained mandibular overdentures “Khao Aroi” in Kamphaeng Phet hospital from 15 October 2012 to 30 July 2016, by collecting information about gender, age, systemic disease, implant location from midline of lower arch, parallel and height of two ball attachments, chewing area and long-term follow-up. The correlation was analyzed by using Fisher’s exact test. Results: There was statistically significant correlation between the height of two ball attachments and the chewing area with the deterioration of ball attachment system on dental implants (p<0.05). It revealed that patients with uneven height of two ball attachments and patients with improper chewing area encountered the deterioration of ball attachment system. The position of two implants from midline of lower arch and the chewing area were found to be significantly correlated with the condition of peri-implant tissue (p<0.05). Patients with unequal gap between each implant and patients with improper chewing area had peri-implant mucositis or peri-implantitis. However, there was no correlation between gender, age and systemic disease with the deterioration of ball attachment system or peri-implant tissue. Conclusion: The height of two ball attachments was a factor affecting the deterioration of ball attachment system on dental implants. The position of two implants from midline of lower arch also affected the peri-implant tissue. Moreover, the chewing area also influenced the deterioration of ball attachment system on dental implants and the peri-implant tissue.